Boosting workplace happiness among married working women through employees training and career growth - Hashim, Junaidah; Wok, Saodah (2015)
This study investigates the extent to which work-related training effects career growth of married women employees in Kuala Lumpur, Malaysia, and in turn how career growth will influence their workplace happiness. Career growth was hence tested as a mediator. Quantitative research was employed using survey method. The measures regarding training and development and career growth were adapted from Huselid (1995) and workplace happiness from Albano (2009). All these measures were reliable with Cronbach alpha values greater than 0.70. The results showed that training and development activities have positive moderate relationship with workplace happiness. Career growth partially mediated the relationship between training and development and workplace happiness. This study implies that training and development is an important activity which promotes career growth among women. Career growth was found to have partial mediating effect on training and workplace happiness of women employees. Even if the women, after receiving training and development, did not achieve career growth and advancement in the same organisation, but with the acquired knowledge, skills, and abilities they stand a better chance for a better position elsewhere.